“Leaving the Door Open”: Using Rational Emotive Behavior Therapy With Sport Climbers Who Experience Fear - Kathryn Lumby; Lindsay Woodford; Martin J. Turner (The Sport Psychologist, 2026)
Climbing is one of the fastest growing sports in the world. As a high-risk sport, climbers are likely to experience fear (an emotional response to threat), yet we understand little about how climbers experience fear, how this impacts performance, and what beliefs underpin this experience. The current study aimed to explore how rational emotive behavior therapy could help sport climbers who experience fear. Five sport climbers participated in a series of rational emotive behavior therapy workshops, and three were interviewed. The findings from an interpretative phenomenological analysis of the data suggest that fear was not helpful for performance and was related to pressure to perform, not danger to physical safety. A tentative finding was that rational emotive behavior therapy gave the sport climbers space and freedom from these expectations, allowing exploration and enjoyment. Practical recommendations are discussed.